الضوابط الشرعية للألعاب الرياضية المعاصرة (University of Mosul-college of Basic Education, 2008)
أباح الإسلام العاب الصراع والدفاع عن النفس ضمن ضوابط وأحكام حتى يتجنب تعرض الشخص للأذى ولم تأتِ إباحتها إلا لإعداد الجسد للقتال في سبيل الله تعالى ودفاع الشخص عن نفسه في أمور حياته وهنالك ضوابط قد وضعها علماء المسلمين لمن يمارس هذه الألعاب حتى تصل إلى الإباحة لمن يمارسها وقد حرم العلماء كل ما هو مضر للإنسان من الألعاب الخطرة. أما ألعاب الكرة والمضرب فقد قيد العلماء هذه الألعاب بضوابط شرعية حتى يخرج لاعبها أو متابعها من دائرة تضييع الواجبات الشرعية، وإن خلت من المحذورات فلا بأس بتعلمها وممارستها عند العلماء.Islam allows people to practice the games of wrestling and self defence with some constraints to avoid people any harm. The permission came from the need to train the body who to fight for the sake of God and self defence. Muslim religious scholars put some constraints on practicing these types of sports which must be followed in order for these permissions not to become rakish. Those games which cause harm to human being are taboo (forbidden), whereas games, like tennis are regulated by religious constraints that don't let the individual forget his religious duties. However, if these types of sports do not include any taboo practices, they are allowed to be learned or practiced.